Pengembangan Media E-Komik Untuk Meningkatkan Pemahaman Konsep Matematika Siswa - Ani Afifah; Putri Arisca Dewi (Universitas Islam Jember, 2022)
This study aims to develop e-comic media with a contextual approach to the material of quadrilaterals and triangles to help improve the understanding of mathematical concepts for seventh grade junior high school students. The development model used by the Thiagarajan model known as the 4-D model was modified into a 3-D model which only reached the third stage, namely define, design, and develop, because it was adapted to the needs of learning media development. The media development process uses Inkscape for coloring and finishing e-comics. E-comic media uses a contextual approach where practice questions are related to everyday life. The e-comic in this study consists of two series, namely series 1 with material on properties, diagonals, sides and angles in quadrilaterals and triangles, in series 2 with material on perimeter and area of ​​quadrilaterals and triangles. The results show that e-comic is valid based on validation assessment, effective based on the percentage of complete learning and practical from the results of observation of implementation. This e-comic media can help students' understanding based on 3 levels, namely translation, intrapolation and extrapolation. The use of e-comic media in learning is intended to build students' understanding of the material presented. Keywords: e-comic, understanding mathematical concept